Sarcoidosis of tongue - Raghuram Pitti; Ramesh Kumar; Saravana S Selvam; Eswar Nagaraj (Wolters Kluwer Medknow Publications, 2012)
Sarcoidosis is a rare, acquired systemic granulomatous disease, with unknown etiology affecting multiple organs and tissue. A 40-year-old male with the previous history of pulmonary sarcoidosis was screened with the clinical presentation of erythematous and nodular lesion over the tongue. Incisional biopsies from the tongue revealed the presence of 'noncaseating epithelioid cell granulomas with Langerhans type multinucleated giant cells' histopathologically. The 24 hours urine calcium examination revealed increased calcium level of 538 mg suggestive of oral sarcoidosis. The patient is periodically reviewed to study the course of the disease and identify the systemic progression at the illness